Performance evaluation of private universities based on balanced scorecard: empirical study based on Iran - Zolfani, Sarfaraz Hashemkhani; Ghadikolaei, Abdolhamid Safaei (Journal of Business Economics and Management, 2013)
Private universities are new generation of universities in Iran that their existences are less than 20 years. The research in this area was never completed about evaluating of these universities all these years. The aim of this research is to make a framework for evaluating these universities with Balanced Scorecard (BSC) and MCDM methods. Three MCDM methods are applied in this research. DEMATEL is applied for research on cause and effect relations of perspectives of BSC, ANP is applied to calculate weights of indices in perspectives and finally VIKOR for ranking universities that is selected as a case study. This research totally used 38 experts in two groups for evaluating of universities. Results of this research are: (1) Internal Process is the most effective perspective of BSC. (2) Brand, Academic Excellence, Product Quality, Student Satisfaction and Budget Control are five more important indices that calculated with ANP. (3) Shomal University of Amol is the best university among five universities that were selected for this research and they have been established more than ten years.